2022
DOI: 10.3389/fphar.2022.1054803
|View full text |Cite
|
Sign up to set email alerts
|

Sanguisorba officinalis L. suppresses non-small cell lung cancer via downregulating the PI3K/AKT/mTOR signaling pathway based on network pharmacology and experimental investigation

Abstract: Background: Non-small cell lung cancer (NSCLC) is the most common type of lung cancer. Sanguisorba officinalis L. (SOL), a traditional Chinese herbal medicine called Diyu, has been shown to have potent antitumor effects. However, the role of SOL in suppressing NSCLC remains unknown.Methods: Network pharmacology was employed for acquiring the potential targets and mechanisms of SOL in NSCLC. Based on the predictions of network pharmacology, we used CCK8 and EdU assays to investigate cell proliferation, flow cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Animal experiments in the present study were authorized by the Center for Experimental Animal of Southwest Medical University, and all experimental procedures were approved by the Ethics Committee of Southwest Medical University [ 13 ] (license No. 20180309091).…”
Section: Methodsmentioning
confidence: 99%
“…Animal experiments in the present study were authorized by the Center for Experimental Animal of Southwest Medical University, and all experimental procedures were approved by the Ethics Committee of Southwest Medical University [ 13 ] (license No. 20180309091).…”
Section: Methodsmentioning
confidence: 99%
“…Ginkgetin is a bioflavonoid extracted from Ginkgo biloba leaves, which exhibits a variety of bioactivities, such as anti‐inflammatory, antitumor, neuroprotective, and antioxidant properties (Adnan et al, 2020; Baek et al, 2016; Pan et al, 2019; Zhang et al, 2017). Mechanistic studies have revealed that ginkgetin induces cell autophagy and apoptosis and inhibits Wnt/β‐catenin, JAK2/STAT3, NFκB/P53, and Nrf2/HO‐1 signaling pathways (Liu et al, 2023; Lou et al, 2021; Pan et al, 2019; Wu et al, 2023). According to the pathogenesis of liver fibrosis and HSC activation, we hypothesized that ginkgetin may have antifibrotic potential.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic studies have revealed that ginkgetin induces cell autophagy and apoptosis and inhibits Wnt/β-catenin, JAK2/STAT3, NFκB/ P53, and Nrf2/HO-1 signaling pathways (Liu et al, 2023;Lou et al, 2021;Pan et al, 2019;Wu et al, 2023). According to the pathogenesis of liver fibrosis and HSC activation, we hypothesized that ginkgetin may have antifibrotic potential.…”
mentioning
confidence: 98%
“…Maintaining the cellular redox balance is dependent on the balance between ROS generation and ROS consumption by antioxidant systems (e.g., GPx and TrxR) [29][30][31][32]. ROS is a double-edged sword; at low concentrations, ROS may function as a pro-tumorigenic signaling molecule, while at high ROS concentrations, it may act as a signaling molecule due to its deleterious, genotoxic, and even pro-apoptotic effects on cancer cells and may act as a cancer regulator [33][34][35][36]. LncRNAs play a role in regulating redox homeostasis in cancer cells by coordinating ROS [37].…”
Section: Introductionmentioning
confidence: 99%